Novelties in the genus Verbascum (Scrophulariaceae) from Greece - Zografidis, Aris; Tyler, Torbjörn; Doğru-Koca, Asli; Cheminal, Alexian; Dimopoulos, Panayotis (Phytotaxa, 2025)
A forthcoming taxonomic treatment of the genus Verbascum in Greece in the frame of The Flora of Greece Project necessitates the description of one species and two subspecies as new to science, the upgrading to subspecies rank of two taxa formerly recognized as varieties, as well as the formation of two new combinations. Verbascum bolbes from the regional unit Thessaloniki is here described as a new species, whereas V. lychnitis subsp. goulimyi and V. undulatum subsp. suffruticosum from the regional units Serres and Corinthia, respectively, are new subspecies. Furthermore, V. longifolium subsp. samaritanii and V. longifolium subsp. pannosum represent new statuses, whereas V. glandulosum subsp. doiranense and V. macrurum subsp. pannosiforme are the new combinations. Importantly, we also show that the name V. pycnostachyum is misapplied in the East Aegean region as Greek subpopulations do not belong to this species but to the morphologically allied V. davisianum described from Anatolia. We additionally perform the lectotypification of the names V. davisianum and V. glandulosum subsp. doiranense.